The Prevalence of Adverse Childhood Experiences in Payatas, an Urban Poor Community in the Philippines - Yanro Judd C. Ferrer; Roy Moore (Philippine Social Science Journal, 2020)
This paper aimed to determine the prevalence of Adverse Childhood Experiences (ACEs) in Payatas, an urban poor community in Quezon City, Philippines. In total, 260 people were surveyed in two areas of Payatas. The results of these surveys were then compared with existing ACE Surveys in other communities. Results found that ACEs were reported at significantly higher levels than in existing surveys, which were typically made of Middle-Class populations. The discrepancy grew at higher ACE Scores. Moderate childhood trauma, ACE Scores of 4 or more, was reported as two to five times more common in our Payatas populations than in the existing survey populations. Severe childhood trauma Scores are less available; however, these trends appear to grow at higher ACE Scores. These results suggest that ACEs are far more common in urban poor communities. That ACE Scores are higher in poorer communities is not a surprising finding. However, the scale of the problem is highly significant. As ACEs are a major root cause of many social problems, including, but not limited to, addiction, teen pregnancy, domestic violence, depression, attempted suicide, and drug abuse, it does indicate a strong area for effective support. The potential for improving the well-being, quality of life, and life expectancy through this framework is large, provided appropriate investment is made in these communities.